Octacosanoic acid, long chains saturated fatty acid from the marine sponges Xestospongia sp. - Mohamad, Habsah; Wan Abdul Jamil, Wan Ainur Najmiah; Abas, Faridah; Mohamad, Khamsah Suryati; Ali, Abdul Manaf (Universiti Putra Malaysia Press, 2009)
Octacosanoic acid has been isolated from the marine sponges Xestospongia sp. collected from Bidong Island, Terengganu. The structure was elucidated using various spectroscopic techniques (IR, MS, 1 H NMR and 13 C NMR). The structure and bioactivities of this long chains saturated fatty acid compound were reviewed.